Conservation of Native Pacific Trout Diversity in Western North America. Issue 6 (2nd June 2016) - Penaluna, Brooke E.; Abadía-Cardoso, Alicia; Dunham, Jason B.; García-Dé León, Francisco J.; Gresswell, Robert E.; Luna, Arturo Ruiz; Taylor, Eric B.; Shepard, Bradley B.; Al-Chokhachy, Robert; Muhlfeld, Clint C.; Bestgen, Kevin R.; Rogers, Kevin; et al.
Abstract : Pacific trout Oncorhynchus spp. in western North America are strongly valued in ecological, socioeconomic, and cultural views, and have been the subject of substantial research and conservation efforts. Despite this, the understanding of their evolutionary histories, overall diversity, and challenges to their conservation is incomplete. We review the state of knowledge on these important issues, focusing on Pacific trout in the genus Oncorhynchus . Although most research on salmonid fishes emphasizes Pacific salmon, we focus on Pacific trout because they share a common evolutionary history, and many taxa in western North America have not been formally described, particularly in the southern extent of their ranges. Research in recent decades has led to the revision of many hypotheses concerning the origin and diversification of Pacific trout throughout their range. Although there has been significant success at addressing past threats to Pacific trout, contemporary and future threats represented by nonnative species, land and water use activities, and climate change pose challenges and uncertainties. Ultimately, conservation of Pacific trout depends on how well these issues are understood and addressed, and on solutions that allow these species to coexist with a growing scope of human influences.